Assessment of circulating Wnt1-inducible signaling pathway protein 1 (WISP1) in obesity and type 2 diabetes mellitus patients - Nada S. Habib; Mohamed H. EL-Hefnawy; Hala O. El-Mesallamy (Ain Shams University, 2018)
Wnt-inducible signaling pathway protein 1 (WISP1) is a recently identified adipokine that is thought to be involved in mechanisms linking obesity and type 2 diabetes mellitus (T2DM). This study is designed to investigate the correlation between WISP1 serum levels and glycemic parameters in Egyptian population subjects for the first time. Anthropometric parameters, routine biochemical markers, serum levels of WISP1, insulin, proinsulin, and high sensitivity C-reactive protein (hs-CRP) were measured by ELISA kits in 90 subjects (24 non-obese patients with T2DM and 22 obese patients with T2DM compared with 24 healthy volunteers and 20 obese volunteers without T2DM. Serum WISP1 levels were significantly higher in obese patients compared with healthy controls (p<0.05). WISP1 was significantly correlated to waist circumference (WC) and serum triglycerides (TG). In conclusion, WISP1 might be a pivotal biomarker linking obesity and T2DM.